Pemesinan Laju Tinggi dan Pemesinan Kering Menggunakan Pahat Karbida pada Bahan Aluminium 6061 - Bobby Umroh; Surya Murni Yunus; Syamsul Basri (Institute of Research and Community Outreach, Petra Christian University, 2013)
Research of high speed machining and dry machining use for the best cutting conditions on the roughness aluminum 6061 material surface using a carbide tool. Collection machining test data is performed 4 times trial with 3 main variable is the rate of cutting (V), Ingestion rate (f) and depth of cut (a) at three levels of scale. The best surface roughness conditions is determined by the rate of the cemetery, where the rate of feeding is recommended at f = 0.12 mm/rev or < 0:17 mm/rev. Effect of cutting force is inversely proportional to the value of rate of cuts. At the greater of the cutting force so the surface roughness also getting smaller. Depth of cut and rate cuts also affects on the surface roughness but not in any condition determined. At the lowest state with V = 1000 m/min f = 0:12 mm/rev and a = 1 mm, surface defects (surface defect). Possibly, this is caused by the vibration of the tool due to lack of dynamic balance in the cutting process.